1987
DOI: 10.1073/pnas.84.15.5439
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 5-fluorouracil to an N-cholyl-2-fluoro-beta-alanine conjugate: previously unrecognized role for bile acids in drug conjugation.

Abstract: Recently we demonstrated clinically significant levels of a previously unrecognized metabolite of the anticancer drug 5-fluorouracil (FUra) in bile ofcancer patients. In the present study, reanalysis of bile from these patients demonstrated the presence of not one but two previously unrecognized metabolites. The major unrecognized metabolite was purified by reversed-phase HPLC, after which its molecular weight was determined by fast-atom-bombardment mass spectrometry to be 497. The similarity in HPLC retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…5). This can also be used to explain why ␤-alanine, the carboxylic acid analog of taurine, is a poor substrate of hBAT (7), whereas both 2-fluoro-␤-alanine (a stronger acid) and taurine are excellent substrates (24). The result is also consistent with previous studies on thioesterases, in which the serine acyl-enzyme intermediate was shown to be unstable relative to the cysteine acyl-enzyme intermediate.…”
Section: Discussionsupporting
confidence: 80%
“…5). This can also be used to explain why ␤-alanine, the carboxylic acid analog of taurine, is a poor substrate of hBAT (7), whereas both 2-fluoro-␤-alanine (a stronger acid) and taurine are excellent substrates (24). The result is also consistent with previous studies on thioesterases, in which the serine acyl-enzyme intermediate was shown to be unstable relative to the cysteine acyl-enzyme intermediate.…”
Section: Discussionsupporting
confidence: 80%
“…Inactive metabolites are derived from initial reduction of the heteroaromatic ring to 5-fluoro-5,6-dihydrouracil and further ring opening to yield the unnatural amino acid α-fluoro-β-alanine (AFBA) as the main product excreted in urine and corresponding to 80-90% of the administered dose. A fraction of AFBA is conjugated in the liver to cholic acid to yield an analog of taurocholic acid, which is possibly associated with the onset of cholestasis in some treated patients (Sweeny et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The low biliary excretion found in IPRL experiments (2.2% a.d.) and the low recovery of radioactive dose measured in the feces after administration of 14 C-CAP to humans (2.6%) (Judson et al, 1999) suggest that, if glucuronidation occurs in humans, it would be a minor CAP detoxification pathway. Since cholestasis has not been described as a side effect of CAP treatment, it is likely that 5Ј-DFCR-G does not affect the physicochemical properties of bile in contrast to what has been observed with a biliary conjugate of FBAL (Sweeny et al, 1987). The third activation step of CAP leads to the formation of 5-FU that occurs mainly via uridine phosphorylase in rodents and thymidine phosphorylase in humans (Ninomiya et al, 1990).…”
Section: Discussionmentioning
confidence: 99%